2018
DOI: 10.1080/23311908.2018.1451610
|View full text |Cite
|
Sign up to set email alerts
|

Work satisfaction, psychological resiliency and sense of coherence as correlates of work engagement

Abstract: The objective of the article is to describe the links between work engagement-the response variable, work satisfaction-the explanatory variable, and sense of coherence, along with resiliency as resources-moderating variables. The theoretical foundations for our hypotheses are Hackman and Oldham's Job Charcteristics Model, Block and Kremen's conception of resiliency, Antonovsky's salutogenesis, the JD-R of relation between work demands and resources and also the model of work engagement in the research of Schau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 30 publications
1
17
0
2
Order By: Relevance
“…직무만족에 관한 연구에서는 기혼취업여성의 직무만족도 가 높을수록 양육 스트레스가 낮고 [9], 우울수준이 낮으며 건 강관련 삶의 질이 높은 것으로 보고되었다 [10]. 또한 직무만족 과 통합력과의 관계 연구에서는 직무만족이 높을수록 통합력 이 높아지는 것으로 보고되었다 [11]. 양육 스트레스는 미취학 자녀를 둔 취업여성에게는 일상생활에서 겪게 되는 주요 스트 레스라 할 수 있는데, 선행연구에서 양육 스트레스는 우울수준 을 높이고 [12], 건강관련 삶의 질을 저하시키는 요인으로 보고 되었다 [10].…”
Section: 연구의 필요성unclassified
“…직무만족에 관한 연구에서는 기혼취업여성의 직무만족도 가 높을수록 양육 스트레스가 낮고 [9], 우울수준이 낮으며 건 강관련 삶의 질이 높은 것으로 보고되었다 [10]. 또한 직무만족 과 통합력과의 관계 연구에서는 직무만족이 높을수록 통합력 이 높아지는 것으로 보고되었다 [11]. 양육 스트레스는 미취학 자녀를 둔 취업여성에게는 일상생활에서 겪게 되는 주요 스트 레스라 할 수 있는데, 선행연구에서 양육 스트레스는 우울수준 을 높이고 [12], 건강관련 삶의 질을 저하시키는 요인으로 보고 되었다 [10].…”
Section: 연구의 필요성unclassified
“…Work engagement corresponds with low values of exhaustion and cynicism, and high values of efficiency ( Schaufeli et al, 2002 ). It has been seen that work engagement (engagement) is greatly influenced by the degree of job satisfaction, where the sense of coherence and, to a lesser extent, resilience are acting as a modulating factor ( Derbis and Jasiński, 2018 ). This resilience can be defined as “the maintenance or rapid recovery of mental health during or after periods of exposure to stress, as a result of a potentially traumatic event, challenging life circumstances, a critical phase of life transition, or a physical illness”.…”
Section: Introductionmentioning
confidence: 99%
“…The scale has established validity and reliability and used in previous studies. [9,15,24] In the current study, Cronbach alpha values for the total scale and each components were .91, .80, .82, and .76, respectively.…”
Section: Measures 231 Sense Of Coherencementioning
confidence: 45%
“…This result is consistent with other studies that have highlighted the impotence of sense of coherence as a source of resilience, and that can buffer the effect of stress in workplace. [15,24,32] A study of Finnish nurse educators found that sense of coherence correlated positively with healthy functioning and job satisfaction, and negatively with perceived job burden and stress symptoms. [22] Individuals with a strong sense of coherence are capable of adapting to stressors in a way that promotes professional commitment as well as their sense of well-being at the workplace.…”
Section: Discussionmentioning
confidence: 99%